Empowering through knowledge: the push for open access (Journal of Patan Academy of Health Sciences, 2024)
Knowledge is the foundation of human progress. However, in the modern academic landscape, access to scholarly publications is often restricted by paywalls and subscription fees. The gatekeeping of academic knowledge behind paywalls positions as a philosophical contradiction to the values of education, justice, progress, equity, and global development. However, public voices have largely been absent from the discussion about open access (OA) of research findings.1 This editorial argues that knowledge dissemination should be free and that academic publications should be openly accessible to ensure equitable access to information, foster innovation, and accelerate global development.